PERANCANGAN BUKU WISATA SEDATI DENGAN TEKNIK FOTOGRAFI SEBAGAI UPAYA DESTINASI WISATA SIDOARJO - Virmadika, Windy; Budiardjo, Hardman; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2017)
Sedati is a kecamatan in Sidoarjo is located in coastal areas that have marine resources in the field of fisheries and ponds to boost the economy of the surrounding community. Subdistrict Sedati is one area that has quite a lot of tourism potential that varies, one artificial tourism, culinary tourism, religious tourism, education tourism and shopping tourism. But the presence of all the tourism potential is not yet known by tourists except the fishing tour that is already known by many tourists outside of the city. Therefore, to demonstrate the potential of its tourism Sedati need for media that can provide information on the whereabouts of tourism potential Sedati, so the presence of the media and information such as tourism potential can be known by the public and tourists can visit these sights, media the right to show the potential of the Sedati that is by designing a travel book Sedati. Sedati is a district in Sidoarjo is located in coastal areas that have marine resources in the field of fisheries and ponds to boost the economy of the surrounding community. Subdistrict Sedati is one area that has quite a lot of tourism potential that varies, one artificial tourism, culinary tourism, religious tourism, education tourism and shopping tourism. But the presence of all the tourism potential is not yet known by tourists except the fishing tour that is already known by many tourists outside of the city. Therefore, to demonstrate the potential of its tourism Sedati need for media that can provide information on the whereabouts of tourism potential Sedati, so the presence of the media and information such as tourism potential can be known by the public and tourists can visit these sights, media the right to show the potential of the Sedati that is by designing a travel book Sedati..This study uses qualitative methods with data collection through observation, interviews, literature, existing studies and collecting data on its potential Sedati to find a concept that suits the character Sedati tourism potential. The concept used in the design of this Sedati travel book is